Open donor nephrectomy via singular pararectal extraperitoneal mini-incision: single-center experience with 425 consecutive cases - Philipp Tessmer; Oliver Beetz; Anna Meyer; Clara A. Weigle; Simon Stoerzer; Gunilla Einecke; Wilfried Gwinner; Florian W. R. Vondran; Felix Oldhafer; Moritz Schmelzle; Nicolas Richter (Renal Replacement Therapy)
Abstract Background Laparoscopic techniques have been successfully implemented for living kidney donation. However, open surgical procedures also yield excellent perioperative outcomes. Endoscopic donor nephrectomy is associated with minimal trauma but is difficult for right-sided nephrectomies. Here, an open nephrectomy approach using a singular pararectal extraperitoneal mini-incision (SPEM) and the perioperative results are presented to elucidate whether open surgery is still justified in the modern era of endoscopic surgery. Methods In this single-center retrospective study, all living kidney donations performed at the Department of General, Visceral and Transplant Surgery of the Hannover Medical School from January 2007 to December 2017 were assessed. Donor characteristics, operation time, transfusion requirements, perioperative complications, and graft outcomes were analyzed. Results Out of a total of 1681 kidney transplantations, 425 living kidney donations (25.2%) were performed. Donors were primarily female (273; 64.2%) and had a median age and body-mass index of 53 (24–76) years and 25.3 (16.8–36.4) kg/m2, respectively. The left kidney was harvested in 50.1% (211) of cases. Median operative time was 95 (48–212) min. Intraoperative transfusion was not required in any of the donors. Intraoperative complications were observed in 2.6% of cases (11), with injury of the donor kidney (5; 1.2%) and acute hemorrhage (3; 0.7%) being the most common complications. Postoperative complications were hematomas (32; 7.7%), seromas (28; 6.7%), and wound infections (7; 1.7%). Except for a single surgical revision owing to colon perforation (1; 0.002%), no other major complications (Clavien–Dindo ≥ IIIa) were observed in any of the donors. The donor’s and recipient’s median estimated glomerular filtration rate at discharge was 55 (29–114) and 51 (14–129) ml/min/1.73 m2, respectively. Initial nonfunction occurred in seven cases (1.6%). Conclusions Unlike the endoscopic technique, SPEM is equally suitable for right- and left-sided nephrectomy. SPEM nephrectomy is safe and results in minimal trauma. Despite performing SPEM nephrectomy in the era of endoscopic surgery, this technique provides excellent results with regard to donor and graft outcomes.